The Effect of Ramadan Fasting on Serum Malondialdehyde Levels as Indicator of Oxidative Stress and Cellular Damage - Annisa Nadia Utami; Risahmawati . .; Muniroh . . (The Avicenna Medical Journal, 2022)
Background: Ramadan fasting is one of five pillars of Islam. Fasting is to refrain from eating and drinking from sunrise (sahur) to sunset (ifthar). Ramadan fasting has been shown to impact on body systems in different manners. One of the benefits of Ramadan fasting is protection against oxidative stress and cellular damage. Malondialdehyde (MDA) is a product of free radicals (hydroxil radicals) with polyunsaturated fatty acids (PUFAs) produced from lipid peroxidation of cell membranes. This paper aims to determine the effect of Ramadan fasting on serum MDA levels.Methods:  The design of this study is quasiexperimental with one group pre and post design. The sample of this study was 16 preclinical students of FK UIN Syarif Hidayatullah Jakarta who performed Ramadan fasting for 17 consecutive days. Blood samples were taken 1 day before Ramadan fasting and 18 days of Ramadan fasting to measure serum MDA levels. The study was conducted in the biochemical laboratory of FK UIN Syarif Hidayatullah.Results: The mean serum MDA levels before fasting was 0.90 ± 0.54 nmol/mL. The median value of serum MDA levels after fasting was 0.43 nmol/mL, with a range between 0.03 - 2.75 nmol/mL. Ramadan fasting decreases serum MDA levels, but the decrease that occurs on the 17th day of Ramadan fasting was not significant (p> 0.05). There was an increase in serum MDA levels in 4 subjects (25%) after Ramadan fasting.Conclusion: Ramadan fasting can reduce serum MDA levels as a marker of oxidative stress and cell damage. Further study is needed to investigate the various results in serum MDA levels after fasting.